Computational insights into the role of external and local electric fields in macrocyclic chemical and biological systems - Mukherjee, Anagh; Ghule, Siddharth; Vanka, Kumar (ChemPhysChem, 2021)
The investigation of the role of the electric field in systems of widespread interest employing computational techniques is an emerging area of research. The outcome of applying an oriented external electric field (OEEF) on the geometric and electronic properties of the chemically unique pi-conjugated cyclic carbon ring compounds has been explored with density functional theory (DFT). Distinct changes in the structural and electronic features of such ring compounds are observed upon the application of OEEFs. Importantly, the calculations indicate that a mixed aliphatic-aromatic conjugated ring converts from a singlet to a triplet after the application of an OEEF, suggesting potential applications in optoelectronics for such molecules, without the need for photochemically induced change in the spin state. Furthermore, the influence of built-in local electric fields (LEFs) present in naturally occurring macrocyclic systems such as valinomycin has also been explored. Static and ab initio molecular dynamics (AIMD) calculations indicate that LEFs are the primary driving factor in determining the energetically favoured position of counter anions such as chloride (Cl-) in the potassium (K+) and sodium (Na+) coordinated valinomycin macrocycle structures: they exist inside the cage in the case of K+ sequestration by valinomycin and outside for Na+. This divergence has been proposed to be the determining factor for the selectivity of the valinomycin macrocycle for binding a K+ cation over Na+.
Keywords: counter anions; Density functional calculations; electric field; ion selectivity; macrocyclic systems